Drivers for flexibility. Three questions to Maureen Andrade and Karen Ferreira-Meyers - Halttunen Timo; Andrande Maureen; Ferreira-Meyers Karen (eucen, 2025)
The global pandemic has affected the lives of everybody and from all walks of life. The world of education is no exception to this, and academics have embraced online and blended learning to meet the urgent needs for increased flexibility in learning and teaching. In this interview we explore the experiences from two contrasting realities to understand the drivers for flexibility. Maureen Snow Andrade is a professor in the Organizational Leadership Department at Utah Valley University. She has an EdD in higher education leadership and is a former associate vice president and associate dean. Her research interests include flexible learning, assessment, global education, leadership, and student access and success. Karen Ferreira-Meyer is an associate professor at the University of Eswatini in Eswatini (the former Swaziland). She is Coordinator of Linguistics and Modern Languages at the Institute of Distance Education (University of Eswatini) and Research Fellow of the University of the Free State (South Africa)